Reseña de: Hoffmeier, James K., Akhenaten and the Origins of Monotheism - Santos Saavedra, Josué (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2018)
Reseña de: Hoffmeier, James K., Akhenaten and the Origins of Monotheism. Oxford University Press, 2015, xvi + 293 pp., ISBN: 978–0–19–979208–5.